EFEKTIFITAS STRUCTURED LEARNING APPROACH (SLA) UNTUK MELATIH KETERAMPILAN SOSIAL SISWA SEKOLAH MENENGAH - , Darmiany (Pendidikan Dasar, 2009)
Abstract:The aim of this study was to develop social-skill training for senior high school students using strategy-development model by Borg and Gall (1983). The development was intended to result in a social-skill training package which could effectively be used by counsellor in developing student’s social skill. The development underwent three stagesof need assessment, training-package development, and evaluation. The package was found to be acceptable in terms of its utility, feasibility, and accuracy in developing student’s social skills. It could thus be used as training material.